Diagnostic Usefulness of Low-Dose Nonenhanced Computed Tomography With Coronal Reformations in Patients With Suspected Acute Appendicitis: A Comparison With Standard-Dose Computed Tomography. Issue 3 (May 2016) - Yun, Seong Jong; Kim, Hyun Cheol; Yang, Dal Mo; Kim, Sang Won; Rhee, Sun Jung; Shin, Jong Soo; Ahn, Sung Eun
Abstract : Purpose: The aims of the study were to evaluate the usefulness of low-dose (LD) nonenhanced CT (NECT) with coronal reformation in diagnosing acute appendicitis and to compare LD NECT with standard-dose (SD) NECT and SD contrast-enhanced CT (CECT). Methods: A total of 452 patients suspected of having acute appendicitis underwent CT using a scan 1 (SD NECT and SD CECT1, n = 182) or a scan 2 protocol (LD NECT and SD CECT2, n = 270). The diagnostic performance and interobserver agreement for diagnosing acute appendicitis were compared. Results: Although the area under the curves of both reviewers of LD NECT were lower than those of SD CECT2, area under the curves of both reviewers for SD NECT were not significantly different for SD CECT1 and LD NECT (all P > 0.05). The interobserver agreements within each scan were excellent (all κ > 0.8). Conclusions: Low-dose NECT with coronal reformation showed high diagnostic performance and can be used as the first-line imaging tool in the work-up of patients with suspected acute appendicitis.